Market participation and rural poverty in Ghana in the era of globlization - Abena D. Oduro; Isaac Osei-Akoto (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
This paper investigates the factors that influence market participation in rural economies. This is based on the premise that participation in the market is an important channel through which the global economy impacts on the rural areas and can have a positive impact on poverty reduction through increased incomes. A case study approach is adopted using four rural communities in three ecological zones of Ghana. – poverty ; case study ; prices ; markets ; rural economy
Keywords: F16; O18; I32; 330; Ländliche Wirtschaft; Ländliche Armut; Ghana